CHANGES IN SOME SYSTEM INDICATORS IN PREGNANT WOMEN WITH GESTOSIS - Kamolova Diyora Djamshedovna; Khusainova Munira Alisherovna (Journals Park Publishing, 2024)
It is well known that gestosis is one of the most dangerous complications of pregnancy and childbirth. Eclampsia is the direct cause of maternal mortality, ranging from 0.21 to 1.4%. However, in Uzbekistan, one of the most disadvantaged countries in this regard, maternal mortality from gestosis increases to 17%, and perinatal mortality to 50%. In the structure of maternal mortality, gestosis firmly occupies the second place and accounts for 24%. The birth of a healthy full-term child with a real serious pathology is observed only in 50-56% of cases. Therefore gestosis remains one of the factors determining the level of perinatal mortality. The indicators of the latter in some regions are in the range of 11.2 – 44.4%, and in preeclampsia and eclampsia they can reach 60%. More than 30 theories have been proposed to explain the etiology of gestosis, however, the nature of their development remains unclear.